Organizational Commitment as a reducer of Turnover Intentions: which component (affective, calculative and normative) is the best predictor? - Moreira, Ana (2021)
This study aims to provide additional empirical evidence on the effect of the three components of organizational commitment on turnover intentions. To this end, we hypothesized that organizational commitment (affective, calculative, and normative) has a significant and negative effect on turnover intentions. A total of 302 participants, employees in different organizations in Portugal, participated in this study. The results revealed a significant and negative effect of affective commitment (AC) and normative commitment (NC) on turnover intentions. Of the three components, affective commitment is the one with the strongest association.